Brushless DC motor driver interfacing with the eZdsp-F2812 fuzzy controller - Nagi F.; Agileswari K.R.; Nagi J. (Taylor and Francis Ltd., 2023)
Readily available low cost brushless DC (BLDC) motor’s integrated drivers – electronic commutation (EC) – encourage engineers to use eZdsp in mechatronic systems by saving them the trouble of developing the motor hardware drivers (inverter with power circuits, optoisolaters, detecting circuits). Commercial motor drivers (EC) improve the hardware reliability of developed system and saves the programmer from writing six pulse-width modulation control sequences code for BLDC motor. Beside saving memory space the processing speed can also be optimised for the application program. In the work presented here a commercial integrated driver is interfaced with eZdsp-F2812 and a fuzzy controller is implemented to control the speed and direction of BLDC motor. Standard available eZdsp libraries “C281xC/C++ Header Files” were modified to accomplish the task described in this work. Necessary hardware and software interfacing techniques between eZdsp-F2812 and motor driver are presented. eZdsp programs and register settings required for clock, timer, counters and interrupt routines are described in detail for motor control and speed measurement. The purpose of this work is to describe the interface process between motor driver (EC) and eZdsp-F2812, define the process limitations and configuration and setup of peripherals registers. © Institution of Engineers Australia, 2014.